1999
DOI: 10.3758/bf03211420
|View full text |Cite
|
Sign up to set email alerts
|

What affects strategy selection in arithmetic? The example of parity and five effects on product verification

Abstract: The parity effect in arithmetic problem verification tasks refers to faster and more accurate judgments for false equations when the odd/even status of the proposed answer mismatches that of the correct answer. In two experiments, we examined whether the proportion of incorrect answers that violated parity or the number of even operands in the problem affected the magnitude of these effects. Experiment 1 showed larger parity effects for problems with two even operands and larger parity effects during the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
155
0
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(184 citation statements)
references
References 49 publications
22
155
0
7
Order By: Relevance
“…The two competing productions are influenced by their prior history of success -that is, how often the production correctly identified a target versus how often it required that the other production apply to confirm that the target was in the other location. 5 Empirically, the notion that procedures will adapt to previous successes and failures has been supported in higher-level domains: for example, deciding whether to search memory or work out the answer (Reder, 1987;Reder & Ritter, 1992), choosing between two problem-solving procedures (Lovett & Anderson, 1996), verifying an arithmetic statement by calculating or using a heuristic (Lemaire & Reder, 1999), or selecting a type of runway in an air traffic controller task (Reder & Schunn, 1999). This account is not completely sufficient, however, in that it would predict that repeated targets would be faster than control targets, and the evidence does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…The two competing productions are influenced by their prior history of success -that is, how often the production correctly identified a target versus how often it required that the other production apply to confirm that the target was in the other location. 5 Empirically, the notion that procedures will adapt to previous successes and failures has been supported in higher-level domains: for example, deciding whether to search memory or work out the answer (Reder, 1987;Reder & Ritter, 1992), choosing between two problem-solving procedures (Lovett & Anderson, 1996), verifying an arithmetic statement by calculating or using a heuristic (Lemaire & Reder, 1999), or selecting a type of runway in an air traffic controller task (Reder & Schunn, 1999). This account is not completely sufficient, however, in that it would predict that repeated targets would be faster than control targets, and the evidence does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…People rejected violations of the parity relationship (i.e., 3 3 4 = 13) more quickly than nonviolations (i.e., 3 3 4 = 14). Other relationships within multiplication, such as the case of five rule (i.e., if either multiplicand is 5, the product must end in 5 or 0; Lemaire & Reder, 1999) and the effect of zero as a multiplicand (e.g., Miller, Perlmutter, & Keating, 1984), also appear to be represented. Second, developmental research on children's strategy selection within an operation has shown that children have rich representations of each operation.…”
Section: Principle Representation Of Mathematical Operationsmentioning
confidence: 99%
“…An exception is the Lemaire and Reder (1999) study, which compared types of problems and found a greater parity effect when both operands were even than when one operand was even, and a reverse, but not significant, effect on 0 X 0 problems. The authors proposed EVENNESS FAMILIARITY EFFECT 359 that noting evenness as a feature invoking the parity rule is twice as likely when there are two even operands; however, no explanation was proposed for the reverse trend noted for two-odd problems.…”
mentioning
confidence: 99%
“…Besides the issues concerning the representation format in which parity information is coded and the way this information is retrieved (Campbell & Clark, 1992;Clark & Campbell, 1991;Dehaene, Bossini, & Giraux, 1993;McCloskey, Aliminosa, & Sokol, 1991;McCloskey, Caramazza, & Basili, 1985), the role of parity in arithmetic has also been studied (Krueger, 1986;Krueger & Hallford, 1984;Lemaire & Fayol, 1995;Lemaire & Reder, 1999). Infact, several studies have proposed that subjects have access and sometimes use parity information without explicit awareness when doing mental calculation.…”
mentioning
confidence: 99%
See 1 more Smart Citation